IMPROVING THE QUALITY OF RESEARCH AND PUBLICATIONS IN SCOPUS JOURNALS FOR LECTURERS AND STUDENTS - Navel Oktaviandy Mangelep; Runtu, Patricia V.; Rumintjap, Fricy O.; Tarusu, Deysti T.; Kambey, Anita Nisa (Community Development Journal : Jurnal Pengabdian Masyarakat, 2025)
The community service activity with the title "Improving the Quality of Research and Publication in the Scopus Journal for Lecturers and Students" aims to improve the ability of lecturers and students to produce quality scientific works, especially for publication in Scopus-indexed international journals. In today’s academic context, publication in international journals is becoming increasingly important, so appropriate support is needed to overcome various challenges faced in the research and writing process of articles. The method applied in this program is a collaborative approach, which includes interactive workshops and direct mentoring by lecturers. Presentation sessions were also organized to share research findings, providing opportunities for participants to learn from each other. The results of this activity showed a significant increase in participants’ understanding of research techniques and how to write good scientific articles. In addition, the program has successfully formed collaborative groups between students and lecturers, which creates high motivation to continue research. The evaluation of participants showed satisfaction with the implementation of the program and expectations to continue similar activities in the future. This activity concludes that the mentoring program not only improves the quality of research but also creates a positive research culture in the academic environment. This is very important for the development of science and the reputation of higher education institutions.